CameraIcon
CameraIcon
SearchIcon
MyQuestionIcon


Question

x2 - 2x + 3 - A = -3x2 + 4x - 9, then A =



A

-4x2 - 6x + 12

loader
B

4x2 + 6x - 12

loader
C

4x2 - 6x + 12

loader
D

4x2 + 6x + 12

loader

Solution

The correct option is C

4x2 - 6x + 12


x2 - 2x + 3 - A = -3x2 + 4x - 9

Thus, -A = -3x2 + 4x - 9 - (x2 - 2x + 3)

-A = -3x2 + 4x - 9 - x2 + 2x - 3

-A = -4x2 + 6x - 12

Hence, A = 4x2 - 6x + 12


Mathematics

Suggest Corrections
thumbs-up
 
0


similar_icon
Similar questions
View More


similar_icon
People also searched for
View More



footer-image